Mechanisms of Cash Dealing in Order to Purchase in Islamic Banks - Muhammad , Muhammad (Islamic Sciences Journal, 2023)
ABSTRACT Man’s issues and goals in his daily dealings over the years do not cease to improve and develop his living condition. The banking transactions are an important part of his modern life, and all these transactions aim at investing and developing money, but this is a type of transaction that differs in Islamic banks from that in other banks, and the goal of Islamic banks is to escape in their dealings from the impurities of usury in all its forms and types. Murabaha is considered one of the most successful, most important and fastest spread in terms of dealing with Islamic banks in order to develop funds. This is because of its advantages that are not available in others. However, serious abuses have been observed in their practical application, which transfers them from permissible to dangerously forbidden, and such abuses must be stopped and avoided. In this research, some images of these abuses were collected, showing how they can be disposed of, while addressing the most important aspects of the Murabaha order to buy in a manner that applies to its adaptation jurisprudence and achieve the required development.